PENGEMBANGAN INSTRUMEN PENILAIAN LOGIKA MATEMATIKA BERBASIS HIGH ORDER THINKING SKILLS UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA - Nina Saswita; Zainal Aziz; Rosliana Siregar (MES: Journal of Mathematics Education and Science, 2022)
This study aims to develop a Higher Order Thinking Skill-based mathematical logic assessment instrument in mathematics to improve student learning independence and to determine the quality of the Higher Order Thinking Skill-based mathematical logic assessment instrument in mathematics to improve student learning independence. The type of research used is Research and Development research with reference to the 4-D model proposed by Thiagarajan, namely define, design, develop, disseminate. The subjects in this study were students of class XI SMK Medan Family Education Foundation. The assessment instrument used is a test of interest in learning and student response questionnaires which will then be tested for feasibility. The results showed that the mathematical logic assessment instrument developed was valid and reliable after being repaired. Meanwhile, after conducting the trial, in the second stage, an effective and practical mathematical logic assessment instrument was obtained.